Antibody-free quantification of seven tau peptides in human CSF using targeted mass spectrometry - Bros, Pauline; Vialaret, Jérome; Barthelemy, Nicolas; Delatour, Vincent; Gabelle, Audrey; Lehmann, Sylvain; Hirtz, Christophe (Frontiers in Neuroscience, 2015)
Tau protein concentration in cerebrospinal fluid (CSF) is currently used as a sensitive and specific biomarker for Alzheimer's disease. Its detection currently relies on ELISA but the perspective of using mass spectrometry (MS) to detect its different proteoforms represents an interesting alternative. This is however an analytical challenge because of its low concentration in the CSF, a biological fluid collected in small volume by lumbar puncture, and with a high structural heterogeneity. To overcome these issues, instead of using immunocapture as previously done, we rather relied on an original two steps pre-fractionation technique of CSF: perchloric acid (PCA) followed by micro solid phase extraction (μSPE). We could then measure seven tau trypsic peptides by Multiple Reaction Monitoring (MRM) on a triple quadrupole mass spectrometer. Quantification was performed using isotopically labeled 15N- recombinant tau protein as internal standard and validated using CSF pools with low, medium, or high tau concentrations (HTCs). Repeatability, intermediate precision, linearity, limit of quantification (LOQ), and recovery were calculated for the different peptides. This new MRM assay, which allowed for the first time CSF tau protein quantification without immunocapture, has important potential application to follow tau metabolism in both diagnostic and therapeutic research.